The Development of Virtual Reality-Based Basketball Arbitration Simulation Tools - Alief Iskurniawan, Moh; Sugiharto, Sugiharto; Baitul Mukarromah, Siti (Journal of Physical Education and Sports, 2020)
The use of science and technology development in sports has an important role in updating refereeÃ¢â‚¬â„¢s knowledge. One of them is media application in basketball which is applied in the form of virtual reality web tools and applications. The virtual reality web tools and applications are designed to facilitate in determining the signals of violations during basketball games. This research is development research. The new product development procedure includes analysis of: the product which will be developed, developing the initial product, expert validation and revision, small-scale trials and revision, large-scale trials, and the final product. The data collection was carried out using questionnaires obtained from expert evaluation, as well as using field observations obtained from basketball referees. The data analysis technique used descriptive percentage analysis. The results of the research on the use of virtual reality web tools and applications obtained results by material experts I, II, and III overall get the Ã¢â‚¬Å“very goodÃ¢â‚¬Â category, with an average score of 4.7. In the small-scale trial, the referee scored the Ã¢â‚¬Å“very goodÃ¢â‚¬Â with a percentage of 97%. In a large-scale trial, the referee received the Ã¢â‚¬Å“very goodÃ¢â‚¬Â category rating with a percentage of 97%. Based on the results, it can be concluded that the product development tools and virtual reality web applications can facilitate the referees to determine violation signals in the implementation of basketball games. Regarding the virtual reality web tools and applications development, It is expected that it can begin to be applied in basketball and bring up new ideas for the virtual reality web tools and applications development.